THE RELATION OF MATHEMATICAL COMMUNICATION AND LEARNING MOTIVATION TO STUDENTS' PROBLEM-SOLVING SKILLS - Iman Putra Sumadi; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This study aims to reveal the positive and significant relationship of mathematical communication and learning motivation to the problem-solving skills of Grade X Science Class Students at SMA Pondok Pesantren Modern Muhammadiyah Boarding School Yogyakarta in the academic year of 2018/2019. This is quantitative research. The research subjects are the Grade X of Science 4 Class Students at SMA Pondok Pesantren Modern Muhammadiyah Boarding School Yogyakarta in 2018/2019, as many as 36 people. The data is obtained through a test and questionnaire. The implemented instrument tests are validity and reliability test. The data analyzed using the descriptive method, statistical test, and hypothesis test. The result of the t-test on variable X1 toward Y with value > table or 1.77102 > 1.69092 shows a positive and significant relationship of mathematical communication to students' problem-solving skills. The result of t-test X2 toward Y with value > ttable or 2.29088 > 1.69092 shows a positive and significant relationship of learning motivation to students' problem-solving skills. The result of F-test X1, X2 toward Y with Fvalue > Ftable or 3.36743 > 3.28492 shows that there is a positive and significant relationship of mathematical communication and learning motivation to students' problem-solving skill.